On Using a STEAM Project-based Learning Model for Secondary School Students: Design, Development and Evaluation - Sarkar, Shivalika (SCHOOL SCIENCE, 2020)
There has been much talk about using the STEAM pedagogy to promote active learning and achieve the desired competencies. However, bringing STEAM pedagogy into the classroom can be a challenging task. A STEAM pedagogical model on project-based learning for the secondary level is discussed in this paper. Through a carefully designed interdisciplinary project named "Our Sun," the elements of STEAM were brought into the high school science classroom. The model was also tested on 80 students of a school in Icchawar Block, Sehore District of Madhya Pradesh. The PBL approach is effective in providing hands-on experience to the students as well as in developing other skills like creativity, inquiry, sharing, debating of ideas within a learning community. It was found that this approach goes in line with the principles of STEAM.